Constructing 0D FeP Nanodots/2D g‐C3N4 Nanosheets Heterojunction for Highly Improved Photocatalytic Hydrogen Evolution. Issue 24 (21st October 2019) - Zhao, Chengxiao; Tang, Hua; Liu, Wei; Han, Chenhui; Yang, Xiaofei; Liu, Qinqin; Xu, Jingsan
Abstract: Two‐dimensional polymeric graphitic carbon nitride (2D g‐C3 N4 ) nanostructures have emerged as a very promising family of photocatalysts for hydrogen evolution from water. Nonetheless, fast recombination of photogenerated charge carriers and the sluggish kinetics of hydrogen evolution reaction (HER) result in unsatisfied solar‐to‐hydrogen efficiency. It is thus greatly encouraging to explore low‐cost and high‐performance co‐catalysts to accelerate the charge transport and to improve the catalytic performance. In this work, for the first time, we report on the fabrication of ultra‐small zero‐dimensional (0D) FeP nanodots anchored on layered 2D g‐C3 N4 nanosheets with well‐defined nanostructures and intimate 0D/2D contact interface. The outstanding feature of the material is that the obtained multidimensional heterojunction photocatalysts reveal highly efficient visible‐light‐responsive HER performance in the absence of noble metals. Under an optimal percentage of 4 wt. % FeP, the FeP/g‐C3 N4 hybrid showed a remarkable hydrogen‐evolving rate of 215 μmol g −1 h −1 and excellent recycling stability, surpassing noble‐metal Pt modified g‐C3 N4 (155 μmol g −1 h −1 ). The enhancement in HER activity is attributed to the synergistic effects of FeP nanocrystals on the improvement of light‐harvesting property in the visible light region and the acceleration of charge carrier dynamics by well‐constructed interfaces. Abstract : FeP nanodots : Novel 0D FeP nanocrystal/ultrathin few‐layer 2D g‐C3 N4 nanosheet heterojunctions were successfully fabricated by a facile two‐step approach. The obtained nanocomposites revealed highly enhanced solar‐driven photocatalytic hydrogen evolution efficiency without using Pt‐based cocatalyst. The improvement in the hydrogen‐evolving performance is credited to synergistic effects between well‐constructed 0D/2D interfaces.